THE USE OF MANGROVE STANDS FOR SHRIMP POND WASTE-WATER TREATMENT - Taufik Ahmad; Mohammad Tjaronge; Fuad Cholik (Research Center for Fisheries, 2001)
Degraded coastal environmental quality due to mangrove forest conversion is strongly suspected as a cause of the decline of shrimp pond productivity in lndonesia.